Student Self-Disclosure through Instagram Posts to Enhance Classroom Interaction - Susanto, Putu Chris; Anditawan, I Made (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Self-disclosure has been widely researched asa way to enhance interactions in the classroom and toimprove the overall learning experience. Student selfdisclosure can be expressed through various media, one ofwhich is social media. Instagram, an indisputably visualplatform of social media interaction, has become immenselypopular among Millennials and Gen Z-ers. This study aimsto analyze the visual aspect of self-disclosing posts from 180students in two universities in Bali Indonesia, under theInstagram hashtag of “#myworld”, conducted at thebeginning of a semester term. Utilizing content analysismethod employing two coders with substantial inter-raterreliability (Cohen Kappa > 0.61), the study finds that thetypology of self-disclosure falls into three categories:descriptive, evaluative, and topical, with descriptive selfdisclosure as the clear majority (82.8%). The themesemerging from the self-disclosing posts include (from thehighest prevalence): family, friends, religion, hobby, self,significant other, things/possession, and work/study.Further qualitative inquiry reveals that self-disclosurethrough social media is perceived to have lower risk thandirect, face-to-face disclosure. It has the potential to be usedto get better acquainted to one another with lower perceivedrisk